Tuning in C‐nociceptors to reveal mechanisms in chronic neuropathic pain. Issue 5 (11th May 2018) - Jonas, Robin; Namer, Barbara; Stockinger, Lenka; Chisholm, Kim; Schnakenberg, Mark; Landmann, Gunther; Kucharczyk, Mateusz; Konrad, Christoph; Schmidt, Roland; Carr, Richard; McMahon, Stephen; Schmelz, Martin; et al.
Abstract : Objective: Develop and validate a low‐intensity sinusoidal electrical stimulation paradigm to preferentially activate C‐fibers in human skin. Methods: Sinusoidal transcutaneous stimulation (4Hz) was assessed psychophysically in healthy volunteers (n = 14) and neuropathic pain patients (n = 9). Pursuing laser Doppler imaging and single nociceptor recordings in vivo in humans (microneurography) and pigs confirmed the activation of "silent" C‐nociceptors. Synchronized C‐fiber compound action potentials were evoked in isolated human nerve fascicles in vitro. Live cell imaging of L4 dorsal root ganglia in anesthetized mice verified the recruitment of small‐diameter neurons during transcutaneous 4‐Hz stimulation of the hindpaw (0.4mA). Results: Transcutaneous sinusoidal current (0.05–0.4mA, 4Hz) activated "polymodal" C‐fibers (50% at ∼0.03mA) and "silent" nociceptors (50% at ∼0.04mA), intensities substantially lower than that required with transcutaneous 1‐ms rectangular pulses ("polymodal" ∼3mA, "silent" ∼50mA). The stimulation induced delayed burning (nonpulsating) pain and a pronounced axon‐reflex erythema, both indicative of C‐nociceptor activation. Pain ratings to repetitive stimulation (1 minute, 4Hz) adapted in healthy volunteers by Numeric Rating Scale (NRS) –3 and nonpainful skin sites of neuropathic pain patients by NRS –0.5, whereas pain even increased in painful neuropathic skin by approximately NRS +2. Interpretation: Sinusoidal electrical stimulation at 4Hz enables preferential activation of C‐nociceptors in pig and human skin that accommodates during ongoing (1‐minute) stimulation. Absence of such accommodation in neuropathic pain patients suggest axonal hyperexcitability that could be predictive of alterations in peripheral nociceptor encoding and offer a potential therapeutic entry point for topical analgesic treatment. Ann Neurol 2018;83:945–957